Manipulative tactics in the headlines of modern Ukrainian web publications - Vydaichuk, T.; Vydaichuk, K. (Studia Philologica, 2021)
This article considers manipulative tactics used in publications’ headlines and discusses a number of consequences of manipulations in mass media. The paper differentiates verbal and nonverbal techniques and mechanisms of impacting addressees. Speech manipulation is defined as conscious and purposeful use of language means which provides the speaker with certain benefits from communication. Speech influence is regarded as manipulation directed at a listener or reader in a particular communicative situation pursuing a maximum desired effect. The article argues that lexical, grammatical and stylistic language means have a powerful influential potential and are capable of attracting an addressee’s (either listener’s or reader’s) attention to some specific meanings thus manipulating and impacting them. Linguistic manipulative methods and techniques in headlines involve a well-thought-out structure of the headline (including collocations, eye-catching or buzz phrases), purposely chosen vocabulary, stylistic means and figures which can influence and stimulate human feelings and emotions that trigger a particular view on the described situation. One of manipulation methods is the creation of anonymous authority or distraction from the essential context of the message with the help of rumors, sensations, advertising, gossip, etc., which complicates the perception of the material read. The article considers the method of contrast a means of attracting the reader’s attention. The paper discusses the means of creating subjective modality as another manipulative tool employed in the headlines. The article focuses on the typical linguistic and stylistic means used in the headlines for the purpose of manipulation: idioms, emotionally colored vocabulary, stylistically and socially marked units, syntactic stylistic devices of antithesis, tautology etc. The paper distinguishes such nonverbal manipulative means within the headlines’ structure as different fonts and colors, images and quotation marks etc. Key words: language manipulation, language influence, media discourse, Ukrainian language, headlines, online edition.